2021
DOI: 10.3920/wmj2019.2548
|View full text |Cite
|
Sign up to set email alerts
|

Serological biomarkers of zearalenone exposure in beef heifers receiving anti-mycotoxin additive

Abstract: The inclusion of anti-mycotoxin additives (AMA) in the diet of production animals has been widely used to avoid mycotoxin exposure. In order to confirm the efficacy of such products in vivo, measurement of mycotoxins and/or their metabolites in biological fluids is preconized. This study aimed at determining the serological biomarkers of zearalenone (ZEN), α-zearalenol, β-zearalenol, α-zearalanol, β-zearalanol (β-ZAL) and zearalanone, to evaluate the efficacy of an AMA in beef heifers. The trial lasted 37 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The former study showed that the two bentonites were able to reduce https://www.wageningenacademic.com/doi/pdf/10.3920/WMJ2021.X003 -Sunday, September 19, 2021 9:29:13 PM -IP Address: 44.224.250.200 the ZEN induced cytotoxicity both in Caco-2 and PHP 1 cells (Nones et al, 2021). The in vivo study showed that β-zearalanol can be used as a biomarker of ZEN exposure via diet to evaluate anti-mycotoxin additives (Tonini et al, 2021).…”
Section: Control Strategies To Reduce the Impact Of Mycotoxicosismentioning
confidence: 99%
“…The former study showed that the two bentonites were able to reduce https://www.wageningenacademic.com/doi/pdf/10.3920/WMJ2021.X003 -Sunday, September 19, 2021 9:29:13 PM -IP Address: 44.224.250.200 the ZEN induced cytotoxicity both in Caco-2 and PHP 1 cells (Nones et al, 2021). The in vivo study showed that β-zearalanol can be used as a biomarker of ZEN exposure via diet to evaluate anti-mycotoxin additives (Tonini et al, 2021).…”
Section: Control Strategies To Reduce the Impact Of Mycotoxicosismentioning
confidence: 99%